Improving the quality of information generated in the financial statements (Journal of Economic Research & Business Administration, 2018)
The article discusses the main approaches to the formation of financial statements in accordancewith international financial reporting standards and the possibility of using these approaches in thepreparation of financial statements of the company. The current system of accounting and reporting doesnot fully ensure the proper quality and reliability of the information generated in it, and also significantlylimits the possibility of useful use of this information. Therefore, improving the quality of informationgenerated in the financial statements and ensuring guaranteed access to it by interested users remains themain task of reforming accounting. The concept of development of accounting and reporting is aimedat improving the quality of information generated in financial accounting and reporting, and ensuringguaranteed access to it by interested users. A qualitative approach to an enterprise’s strategy should bebased on the fact that quality is both the most effective means of meeting needs and a means of reducingcosts. The first attribute of the quality of information provided in financial statements is that it is readilyunderstandable by a user who has sufficient knowledge of business and economic activities, accountingand a willingness to study the information with due diligence.